Development and characterization of ti-5cu-xnb alloys for biomedical applications - Pandey, Anurag Kumar (IIT(BHU) Varanasi, 2023)
Abstract is available in the content.
Keywords: Development and characterization; ti-5cu-xnb alloys; biomedical applications